2016
DOI: 10.7863/ultra.15.08076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasound‐Guided to Fluoroscopy‐Guided Biceps Tendon Sheath Therapeutic Injection

Abstract: Compared to fluoroscopy-guided biceps tendon sheath injection, ultrasound had higher initial- and final-pass success rates, visualized abnormalities before injection, and had similar pain relief and complication rates. Ultrasound is more accurate and has greater diagnostic benefits than unguided or fluoroscopy-guided biceps tendon sheath injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Petscavage-Thomas and Gustas conducted a retrospective study to compare the effectiveness of US- vs fluoroscopy-guided biceps tendon injection at the groove level. 10 In this study, US guidance had a higher success rate with administration of medication inside the tendon sheath. There was no significant difference in pain relief and complication rates.…”
Section: Long Head Of the Biceps Tendonmentioning
confidence: 59%
“…Petscavage-Thomas and Gustas conducted a retrospective study to compare the effectiveness of US- vs fluoroscopy-guided biceps tendon injection at the groove level. 10 In this study, US guidance had a higher success rate with administration of medication inside the tendon sheath. There was no significant difference in pain relief and complication rates.…”
Section: Long Head Of the Biceps Tendonmentioning
confidence: 59%
“…22 61 65-78 RoB assessment of the retrieved studies is detailed in online supplemental table 3. Imaging Imaging Imaging US versus fluoroscopy [12][13][14][15][16] and 1 study each comparing fluoroscopy with palpation guidance, 53 fluoroscopy with US and palpation guidance, 59 or fluoroscopy with CT-guided interventions, 54 as well as one study comparing either US or fluoroscopy with palpation guidance. 17 The following large joints and periarticular structures were studied: knee (n=10), shoulder (n=9), sacroiliac joint (SIJ) (n=3) and one study each for elbow, wrist, spine, piriformis muscle, hip, trochanteric bursa and ankle.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported better accuracy for needle placement/injectate location (n=8) or synovial fluid acquisition (n=1) using US as compared with palpation-guided injections (seven with moderate RoB 23-26 29 31 56 and two with high RoB), 33 58 while two studies concluded that there was no difference between the two methods (one moderate, one high RoB). 20 32 Results for correct needle placement were heterogenous for comparisons of US with fluoroscopy: one study favoured US for biceps tendon sheath injections (high RoB), 14 one reported better accuracy for SIJ injections using fluoroscopy (high RoB) 15 and another study reported no difference between the techniques for SIJ injections (moderate RoB). 13 Fluoroscopy was superior to palpation-guided injections for injectate location in patients with painful SIJ (low RoB) 53 and superior to CT when assessing the positive rate of discovertebral biopsy cultures at the lumbar spine in patients with osteomyelitis (high RoB).…”
Section: Accuracymentioning
confidence: 99%
See 2 more Smart Citations